Breastfeeding practices among immigrants living in Finland: Results from the FinChildren survey - I Muhumed; J Meinilä; R Klemetti; FA Adebayo; SM Virtanen; M Erkkola (Journal of Migration and Health, 2024)
Background: Breastfeeding is a cornerstone of child health and survival as it provides crucial, non-replaceable nourishment necessary for infant's growth and development. Immigration has been shown to influence breastfeeding particularly among immigrants from low- and middle-income countries. Our aim was to examine breastfeeding practices and sociodemographic characteristics of Somali-, Arabic-, and Russian-speaking in comparison with Finnish-speaking mothers. Methods: We analyzed data from 5348 mothers with infants who participated in FinChildren survey conducted in 2020. Univariate and multivariate analysis were used to estimate the association between maternal origin and breastfeeding practices by comparing immigrant mothers with native-born mothers. Results: Somali-/Arabic-speaking mothers were younger, less educated and had higher BMI than Russian- and native Finnish-speaking mothers. Proportions of exclusive breastfeeding at 4–5 months of age were lowest among Somali-/Arabic-speaking mothers (21 %) compared to native-born (49 %) and to Russian-speaking mothers (52 %). Again, Somali-/Arabic-speaking mothers had the highest proportions of mixed feeding (66 %) compared to native Finnish-speaking (38 %) and Russian-speaking mothers (32 %). Being a Somali-/Arabic-speaking mother decreased the odds of exclusive breastfeeding five times (OR 0.20, 95 % CI 0.10–0.45) and quadrupled (OR 4.0, 95 % CI 2.18–7.37) the odds of mixed feeding at 4–5 months of age. Conclusion: Even though the number of immigrant mothers was low, this study suggests that maternal origin is a significant predictor of suboptimal breastfeeding independent of sociodemographic and antenatal characteristics. There is a need for culturally sensitive interventions to promote breastfeeding among these groups.